(E)-N-(4-Chlorobenzylidene)-5-(4-methylphenyl)-1,3,4-thiadiazol-2-amine - Yu, Peng (International Union of Crystallography, 2011)
The title compound, C(16)H(12)ClN(3)S, was synthesized by the reaction of 5-(4-methylphenyl)-1,3,4-thiadiazol-2-amine and 4-chlorobenzaldehyde. The thiadiazole ring is essentially planar with mean deviation of 0.0042 Å.